Genotype x environment interaction and stability analysis for yield and its components in brinjal (Solanum melongena) - MOHANTY, B K; PRUSTI, A M (The Indian Journal of Agricultural Sciences, 2013)
Yield and its components were studied for genotype x environment interaction and stability parameters in 15genotypes of brinjal over 3 years during 1994-96. Wide difference among genotypes, environments and genotype xenvironment interaction were observed for all the traits. Significant linear and nonlinear components of genotype-environment interaction were recorded fol' yield and number of fruits/plant, while the predictable portion alone was significant for average fruit weight. Adaptability of brinjal genotypes for general cultivation and high-yielding environments were identified. Significant positive correlations were noticed between mean performance and regression coefficient for yield and number of. fruits/plant; mean perfomance and deviation from regression for average fruit weight and between regression coefficient and deviation from regression for average fruit weight and number of fruits/plant.